2011
DOI: 10.1007/s00373-011-1065-7
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning a Graph into Global Powerful k-Alliances

Abstract: A set S of vertices of a graph is a defensive k-alliance if every vertex v ∈ S has at least k more neighbors in S than it has outside of S. Analogously, a set S is an offensive k-alliance if every vertex in the neighborhood of S has at least k more neighbors in S than it has outside of S. Also, a powerful k-alliance is a set S of vertices of the graph, which is both defensive k-alliance and offensive (k + 2)-alliance. A powerful k-alliance is called global if it is a dominating set. In this paper we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…the difference between the number of outside and inside neighbours should be larger than a given constant, the community should also be a dominating set, see e.g. [4,5,15] for overview and further references.…”
Section: Introductionmentioning
confidence: 99%
“…the difference between the number of outside and inside neighbours should be larger than a given constant, the community should also be a dominating set, see e.g. [4,5,15] for overview and further references.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there exist several studies on partitioning graphs into k-alliances and various theoretical results are obtained for some graphs classes in the literature. In this framework, the partitioning of graphs into defensive k-alliances is investigated by Eroh and Gera [20,21], Haynes and Lachniet [22], Yero et al [23], the partitioning into offensive k-alliances is the subject matter of Sigarreta et al [24], Yero [25], and the partitioning into powerful k-alliances is discussed in Slimani and Kheddouci [26], Yero and Rodríguez-Velázquez [27]. In this context, it would be interesting to see how such partitioning can be of interest to solve practical problems.…”
Section: Historical View and Applications Of Alliancesmentioning
confidence: 99%
“…Cartesian product graphs Let G i = (V i , E i ) be a graph of order n i , minimum degreeδ i and maximum degree∆ i , i ∈ {1, 2}. Yero [25] and Yero and Rodríguez-Velázquez [27] studied the powerful k-alliances in Cartesian product graphs and obtained some results for the associated parameters. Thus, they showed that if…”
Section: Path Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then many variatons appeared. The most extensively studied are defensive alliances [9,8,13,19,21], offensive alliances [7,12,18] and powerful or dual alliances [2,3,22]. A more generalized concept of alliance is represented by k-alliances [1,15,16,17,19], and Dourado et al presented a new definition of alliances, namely, (f, g)-alliances [6], that generalizes previous concepts.…”
Section: Introductionmentioning
confidence: 99%